2021
DOI: 10.6018/reifop.467731
|View full text |Cite
|
Sign up to set email alerts
|

Evolución de la atención, concentración y rendimiento académico tras una intervención basada en descansos activos

Abstract: El objetivo principal de la investigación ha sido analizar la evolución de la atención y concentración en jóvenes estudiantes, tras la implementación de un programa basado en descansos activos o Activity Breaks en la asignatura de Lengua Castellana y Literatura. La muestra, compuesta por 31 estudiantes, 14 chicas y 17 chicos, del primer curso de la Enseñanza Secundaria Obligatoria (edad media 12.13 años), se dividió en dos grupo clase: grupo control y grupo experimental. La intervención, de 7 semanas, implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 25 publications
(38 reference statements)
2
5
0
Order By: Relevance
“…As mentioned above, there is controversy among the reviewed studies. Although some studies such as Contreras Jordán et al [ 40 ] and Peiris et al [ 43 ] support the improvement of AP after intervention with AB, the results of the current study coincide with other studies in which the desired AP was also not obtained [ 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Taking Nieto Martín’s [ 11 ] case into account, the results obtained in this paper may be because AP is a multifactorial variable influenced by personal and social factors.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…As mentioned above, there is controversy among the reviewed studies. Although some studies such as Contreras Jordán et al [ 40 ] and Peiris et al [ 43 ] support the improvement of AP after intervention with AB, the results of the current study coincide with other studies in which the desired AP was also not obtained [ 17 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Taking Nieto Martín’s [ 11 ] case into account, the results obtained in this paper may be because AP is a multifactorial variable influenced by personal and social factors.…”
Section: Discussionsupporting
confidence: 87%
“…Research by Bartholomew et al [ 19 ] (mathematics, language arts, and science), Fiorilli et al [ 20 ] (mathematics), Macdonald et al [ 21 ] (mathematics and reading), Magistro et al [ 22 ] (arithmetic reasoning), Mavilidi et al [ 23 ], and Mok et al [ 24 ] reported significant differences between groups following AB interventions. In contrast, research by Arribas-Galarraga et al [ 17 ] (spelling), Donnelly et al [ 25 ] (mathematics, reading comprehension, spelling), Egger et al [ 26 ] (spelling and reading), Erwin et al [ 27 ] (mathematics and reading), Fedewa et al [ 28 ] (mathematics), Mullender-Wijnsma et al [ 29 ] (reading, spelling, mathematics, mathematics speed), Raney et al [ 30 ], Snyder et al [ 31 ], Solberg et al [ 32 ], van den Berg et al [ 33 ], and Young-Jones et al [ 34 ] showed no significant differences between the groups. In addition, Mullender-Wijnsma et al [ 35 ] found a significant effect between the AB and control groups in some of the groups, but not in all groups.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations